Malaria-Transmitting Vectors Microbiota: Overview and Interactions With Anopheles Mosquito Biology - Djihinto, Oswald Y.; Medjigbodo, Adandé A.; Gangbadja, Albert R. A.; Saizonou, Helga M.; Lagnika, Hamirath O.; Nanmede, Dyane; Djossou, Laurette; Bohounton, Roméo; Sovegnon, Pierre Marie; Fanou, Marie-Joel; Agonhossou, Romuald; Akoton, Romaric; et al. (Frontiers in Microbiology, 2022)
Malaria remains a vector-borne infectious disease that is still a major public health concern worldwide, especially in tropical regions. Malaria is caused by a protozoan parasite of the genus Plasmodium and transmitted through the bite of infected female Anopheles mosquitoes. The control interventions targeting mosquito vectors have achieved significant success during the last two decades and rely mainly on the use of chemical insecticides through the insecticide-treated nets (ITNs) and indoor residual spraying (IRS). Unfortunately, resistance to conventional insecticides currently being used in public health is spreading in the natural mosquito populations, hampering the long-term success of the current vector control strategies. Thus, to achieve the goal of malaria elimination, it appears necessary to improve vector control approaches through the development of novel environment-friendly tools. Mosquito microbiota has by now given rise to the expansion of innovative control tools, such as the use of endosymbionts to target insect vectors, known as “symbiotic control.” In this review, we will present the viral, fungal and bacterial diversity of Anopheles mosquitoes, including the bacteriophages. This review discusses the likely interactions between the vector microbiota and its fitness and resistance to insecticides.